Field notes contributed by Robert K. Myers, fall 1986 - Myers, Robert K.et al (1986)
List of birds and locations contributed by Robert K. Myers with observer Stephen J. Dinsmore. The field notes include several bird descriptions. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed